2019
DOI: 10.1016/j.ypmed.2019.105770
|View full text |Cite
|
Sign up to set email alerts
|

The cardiovascular effects of electronic cigarettes: A systematic review of experimental studies

Abstract: This study systematically reviews the evidence of physiological and pathophysiological cardiovascular effects after direct exposure to electronic cigarettes and discusses the implications for cardiovascular disease. Methods Four researchers conducted the review applying Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. 28 Search strategy A literature search was conducted on 17 July 2017 and updated on 12 th June 2019 using Ovid MEDLINE and Embase databases from 1996 to 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 104 publications
(162 reference statements)
0
58
0
4
Order By: Relevance
“…Our umbrella review, poignantly synthesizing the evidence accrued so far from in vitro, in animal, in human volunteers, healthy subjects, and patients on the cardiovascular risk associated with EVC use, either acute or chronic, shows that data are expanding progressively, but several conclusions can already be made on the [25,32]. For instance, oxidative stress, cytotoxicity, and cardiomyocyte dysfunction are established effects of EVC [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our umbrella review, poignantly synthesizing the evidence accrued so far from in vitro, in animal, in human volunteers, healthy subjects, and patients on the cardiovascular risk associated with EVC use, either acute or chronic, shows that data are expanding progressively, but several conclusions can already be made on the [25,32]. For instance, oxidative stress, cytotoxicity, and cardiomyocyte dysfunction are established effects of EVC [33].…”
Section: Discussionmentioning
confidence: 99%
“…Kennedy and colleagues reviewed several experimental and clinical studies on the cardiovascular safety of EVC, highlighting that they may cause oxidative stress, cardiomyocyte dysfunction and mutagenesis, vascular inflammation, endothelial dysfunction, vasospasm, complement deposition, platelet aggregation, adhesion, and activation, with hypertension, tachycardia, arterial stiffening, atherosclerosis and thrombotic risk, albeit less intensely than TCC [25]. Most importantly, they suggested that studies with conflicts of interest were less likely to report adverse events.…”
Section: Recent Findingsmentioning
confidence: 99%
“…Previous studies suggested that E-cigarettes may induce various human diseases, such as lung and bladder carcinoma, and cardiovascular harm 8,9 . However, the correlation between the cytotoxic effects of e-cigarettes and human middle ear diseases is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no evidence that alternative nicotine delivery products are safe: on the contrary. Almost all independent studies indicate potential harm [15,16]. The uncertainty seems to be around the degree of harm rather than the presence of harm related to these products, but we have no evidence on the long-term health effects of using e-cigarettes.…”
mentioning
confidence: 82%